Effect of Heat Treatments on the Corrosion Resistance of Medium Carbon Steel - علي هترة (Latakia University Journal -Engineering Sciences Series, 2023)
The corrosion is one of the important problems that may be occur to the parts of machinery and equipment after manufactured and when used as a result of exposure to corrosive media. Plain-carbon steel is considered as one of the most common minerals used in industrial applications. Some of heat treatments can have direct effect on the corrosion rate of steel by building up galvanic corrosion cells between its microscopic phases. Therefore, to adopt one of kinds of the plain-carbon steel and the most commonly used in industry to be study subject, that is medium carbon steel and took samples of this steel has been treated thermally in three methods which the normalising, annealing, and hardening .The corrosive media used in the research is Sulfuric Spring, it contains many chemical compounds to show its influence on the corrosion of steel. The weight loss method is used to determine corrosion rate and to compare between the results , show that the greatest corrosion resistance of the annealed steel and the corrosion resistance of the hardened steel is the lowest while the corrosion resistance of the normalised steel is in-between them. Calcium carbonate was formed on the metal surface which acts as an isolating layer which decrease corrosion rate with time